Anna O : a novel - Blake, Matthew (Harper, an imprint of HarperCollinsPublishers, 2024)
A forensic psychologist and expert in sleep-related homicides is the last hope for solving a case where a woman with a rare psychosomatic disorder stabbed two people to death while she slept.